High purity fructose from inulin with heterogeneous catalysis – from batch to continuous operation. Issue 2 (22nd August 2018) - Pérez Nebreda, Andrea; Russo, Vincenzo; Di Serio, Martino; Eränen, Kari; Murzin, Dmitry Yu; Salmi, Tapio; Grénman, Henrik
Abstract: BACKGROUND: Inulin is a valuable source of high purity fructose. The conversion of inulin to fructose utilizing an advanced sulfonic ion‐exchange resin was previously investigated in detail in a batch reactor study, where a detailed mechanistic model for the reaction kinetics was demonstrated ( J Chem Technol Biotechnol 2018;93:224–232). The same catalyst was employed in tailor‐made continuous fixed‐bed reactors in the current work in order to study the feasibility of continuous operation. RESULTS: Two types of reactors were utilized: a single‐bed reactor and a multibed reactor with sample withdrawal between catalyst beds. The results from the single‐bed reactor allowed optimal reaction conditions to be determined which were extrapolated and used for experiments in the multiple‐bed reactor. High yields of fructose (75%) were obtained with the multiple‐bed reactor without any degradation products. Detailed flow characterization was performed on the reactor system and residence time distribution results were merged with the detailed model for the chemical kinetics obtained from batch reactor studies taking into account mass transfer limitations, in order to obtain a rigorous model for the performance of the continuous reactor. The fit of the mathematical model to the experimental data was very good and this provides a useful tool for further development and scale‐up purposes. CONCLUSIONS: The results of the two related studies highlight the potential of new reactor design strategies towards the realization of more efficient, sustainable and green processes, which can easily be scaled‐up and implemented in bio‐based industry. © 2018 Society of Chemical Industry